Weighing Risk Factors for Adolescent Victimization in the Context of Romantic Relationship Initiation - Gonzalez-Mendez, Rosaura (Journal of interpersonal violence, 2021)
Research has paid little attention to the link between the characteristics of the relational context where adolescents are likely to initiate their romantic relationships and teen dating violence (TDV). Hence, the findings are still scattered. This study examined different risks in the female teenagers’ relational context (peer group characteristics, participants’ risky activities, and pressure to start dating) and their TDV victimization, which had not been previously studied in the Spanish population. The moderating role of parental monitoring strategies was also analyzed. Participants were 1,248 Spanish female teenagers who completed measures of the aforementioned factors. Highly victimized girls reported having more deviant and older male peers, receiving more pressure to start dating, and using more alcohol and drugs than participants with low victimization did. High parental monitoring was only effective to prevent TDV victimization in low-risk relational contexts. The findings extend prior research by providing evidence of the risk of pressure to start dating and low effectiveness of parental monitoring against high-risk peers. They also highlight the need to reduce specific risks of TDV in the adolescent relational context.